Age-related changes in sperm traits and evidence for aging costs of sperm production in a sexually promiscuous passerine - Míčková, Kristýna; Tomášek, Oldřich; Jelínek, Václav; Šulc, Michal; Pazdera, Lukáš; Albrechtová, Jana; Albrecht, Tomáš (Frontiers in Ecology and Evolution, 2023)
In many animal species, organismal performance declines with age in a process known as ageing or senescence. Senescence typically leads to a deterioration of physiological functionality and can impact the development of primary sexual phenotypes. Sperm production is a complex and costly process that is sensitive to changes in individual physiological state, yet remarkably little is known about age-related changes in sperm performance and ageing costs of sperm production. Here we use a non-linear generalized additive mixed models (GAMM) modelling to evaluate age-related changes in postcopulatory sexual traits in the European barn swallow (Hirundo rustica rustica), a relatively short lived sexually promiscuous passerine species, where male extra-pair fertilization success has been shown to increase with age. We confirmed a positive relationship between sperm midpiece length and sperm velocity in this species. Within-male changes in sperm morphology and sperm velocity were in general absent, with only sperm length decreasing linearly with increasing age, although this change was negligible compared to the overall variation in sperm size among males. In contrast, the cloacal protuberance (CP) size changed nonlinearly with age, with an initial increase between the first and third year of life followed by a plateau. The results further indicate the existence of a trade-off between investments in sperm production and survival as males with large CP tended to have a reduced lifespan. This seems consistent with the idea of expensive sperm production and survival ageing costs associated with investments in post-copulatory traits in this sexually promiscuous species.